Tingkat Kematangan Inti Oosit Sapi Setelah 24 Jam Presevasi Ovarium - Rini Widyastuti; Siti Darodjah Rasad (Agricultural Faculty, 2015)
(Nuclear maturity of bovine oocyte after 24 hours ovary preservation)ABSTRACT. The objective of the research was to investigate their meiotic competence or nuclear maturity of bovine oocytes maturity in vitro after 24 hour preservation on 5C. Oocytes were collected by slicing the ovaries in modified phosphate buffer saline (m-PBS). Selected cumulus-oocyte complexes (COCs) homogenous ooplasm were cultured in maturity medium at 38C in humidified atmosphere of 5% CO2 incubator. After 24 hours, oocytes stained for nuclear maturitys evaluation. The proportion of oocytes at metaphase II (MII) was significantly difference (P 0.05) on oocytes that 24 hours preservated (44.21 3.04%) vs oocytes from fresh ovary (73.97 9.32%) (P0.05). These results indicated that 24 hours preservation bovines ovary on 50C cause decreases of nuclear oocyte maturity.